The East In The Work Of V.A. Djukovskiy - M. M. Bayeshanov (Genius Journals, 2024)
This article examines the influence of the Islam East on the works of the Russian poet V. Djukovskiy. The author analyzes in detail the Eastern motifs in Djukovskiy’s poetry , his translations of European poets on Eastern themes, as well as the influence of Eastern philosophy and culture on his worldview. This study is of interest to a wide range of readers interested in Russian literature, the works of V. Djukovskiy, as well as East-West cultural ties .
Keywords: Islamic East; Russian literature; V.Djukovskiy; Eastern motives